Activities for Prevention of Gyrodactylus Salaris Distribution in the Kola Peninsula Rivers - Kalinina, Natalia; Kravets, Petr (KnE Life Sciences, 2020)
Monitoring of distribution of monogenean ectoparasite Gyrodactylus salaris, dangerous for wild populations of the Atlantic salmon in northwest Europe, is carried out by Veterinary Services and the profile scientific organizations in different European countries. In Murmansk area, Gyrodactylus lavareti was first found in a trout farm in Tuloma River in 1996. From now on, representatives of genus Gyrodactylus are annually identified in farmed fish in Tuloma River, according to ichthyopatholocic observations of salmonid farms in Murmansk area. Species G. salaris was indicated in 2016 in farmed trout in Tuloma River and in wild salmon smolts in Pak River of the Nizhnetulomsky water basin. Throughout a number of years, the experts of Regional Veterinary Service and the scientific organizations of Murmansk area discuss necessity of working out of measures to prevent Gyrodactylus salaris introduction in the rivers of the Kola Peninsula with wild populations of the Atlantic salmon. Any transport of smolt and live fish from the freshwater objects of Baltic Sea basin to the water objects of the Barents Sea basin sea would become the most significant threat by parasite Gyrodactylus salaris distribution and might cause a damage of natural populations of the Atlantic salmon of Kola Peninsula.